2000
DOI: 10.1017/s1446788700002482
|View full text |Cite
|
Sign up to set email alerts
|

Sharp starlikeness conditions for analytic functions with bounded derivative

Abstract: We develop sharp conditions for various types of starlikeness for functions analytic in the unit disk with bounded derivatives. We also describe the precise range [zf '(z)/f (z) : z e D , / € ^} , where / e 3?x means/(0) = 0,/'(0) = 1, and |/'(z) -l| < A. in the unit disc D, and draw some conclusions from that.2000 Mathematics subject classification: primary 30C45.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The numbers 2/5 and 3/10 in Lemma A were proved to be sharp (see for instance , ). We refer to for many other interesting properties of the class R(α,λ).…”
Section: Preliminaries and Main Resultsmentioning
confidence: 97%
“…The numbers 2/5 and 3/10 in Lemma A were proved to be sharp (see for instance , ). We refer to for many other interesting properties of the class R(α,λ).…”
Section: Preliminaries and Main Resultsmentioning
confidence: 97%
“…For example, Ponnusamy and Singh [15] have shown that Uðl; mÞ J S à if m < 0 and 0 a l a 1 À m ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi ffi ð1 À mÞ 2 þ m 2 q ¼: l à ðmÞ and in [8], Obradovic ´proved that the above inclusion continues to hold for 0 < m a 1 and with the same bound for l. The sharpness part of these results may be obtained as a consequence of results from [21]. However, it is not known whether each function f in Uð1; mÞ (or more generally, Uðl; mÞ with l à ðmÞ < l a 1) is univalent in D for certain values of m in the open interval ð0; 1Þ.…”
Section: Introductionmentioning
confidence: 86%